Towards good governance: a half century of India's administrative development - Jain, R.B. (2001)
Since independence, India has undertaken a number of efforts to establish an effective development-oriented, citizen-friendly and responsive system of administration to contribute toward good governance. While the traditional system of public administration was appropriate for the pre-independence period, subsequent social, economic and political changes necessitated radical changes in policies and their implementation. A set of new issues called for a thorough reorientation of the system of public administration. Administrative development had, therefore, to be planned and executed in the face of ever-growing conflicts between various non-state actors/institutions and the state. The strategies for administrative development adopted not only included evolving appropriate politico-administrative institutions for democratic governance, but also a consistent effort on reorienting the formal and informal aspects as well as improving the techno-professional skills of bureaucracy at all levels. In addition to this an appropriate balance and cooperation between the public and private sectors was essential in the context of growing liberalization and globalization. The experience of India emphatically demonstrates that an active and consociational association of citizens at all levels of the governmental structure is critical to the process of modernization of the state and administration. The dispersion of political and administrative power among various groups and regions emerges as a useful strategy for ensuring the continuity of the state and democracy in a vast country with numerous ethnic, religious and linguistic divisions. - Reproduced
Keywords: Public administration - India; Public administration